Development of Mucosal PNAd+ and MAdCAM-1+ Venules during Disease Course in Ulcerative Colitis - Britt Roosenboom; Ellen G. van Lochem; Jos Meijer; Carolijn Smids; Stefan Nierkens; Eelco C. Brand; Liselot W. van Erp; Larissa G.J.M. Kemperman; Marcel J.M. Groenen; Carmen S. Horjus Talabur Horje; Peter J. Wahab (Cells, 2020)
PNAd and MAdCAM-1 addressins on venules are of importance in T-cell homing and potential therapeutic targets in ulcerative colitis (UC). Normally, PNAd+ high endothelial venules (HEVs) are only present in lymphoid organs, whereas small numbers of MAdCAM-1+ venules can be seen in non-lymphoid tissue. We aimed to study their presence in the intestinal mucosa of UC patients at diagnosis and during follow-up, and their correlation with disease activity. Colonic biopsy specimens of 378 UC patients were analyzed by immunohistochemistry for CD3, CD20, ERG, MECA-79 (PNAd) and MECA-376 (MAdCAM-1) and compared to healthy controls (HC). The proportion of PNAd+HEVs in UC at diagnosis was 4.9% (IQR 2.0%–8.3%), while none were detected in HC. During follow-up, PNAd+HEVs completely disappeared in remission (n = 93), whereas the proportion in active disease was similar to baseline (n = 285, p = 0.39). The proportion of MAdCAM-1+venules in UC at baseline was 5.8% (IQR 2.6–10.0). During follow-up, the proportion in remission was comparable to diagnosis, but upregulated (7.5% (IQR 4.4–10.9), p = 0.001) in active disease. In conclusion, PNAd+HEVs appear in UC during active inflammation which could thus serve as a marker for disease activity, whereas MAdCAM-1+venules remain present after inflammation is resolved and increase after subsequent flares, reflecting chronicity and potentially serving as a therapeutic target.